Mikroprosesor Intel 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, Posesor Pentium Pro, Pentium II, Pentium III, dan Pentium 4 : Arsitektur, pemrograman, dan antarmuka - Barry B. Brey (Andi, 2005)
Jilid 1